2007
DOI: 10.1111/j.1440-1746.2007.04903.x
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of MELD as a short‐term prognostic indicator in patients with chronic liver disease: An Indian experience

Abstract: The MELD score was not found to be superior to CTP score and modified CTP score for short-term prognostication of patients with cirrhosis in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…This study shows that in both the CTP classification and the MELD scoring system, a poor prognosis was associated with higher preoperative cytokine concentrations, which suggests that both rating systems are useful for predicting the severity of the systemic inflammatory response in patients with end-stage liver disease. This result is consistent with those of Boin et al (2), Said et al (5), and Mishra et al (20), who suggested that both the CTP classification system and the MELD scores were equivalent for determining the outcome of patients suffering from chronic liver disease.…”
Section: Discussionsupporting
confidence: 92%
“…This study shows that in both the CTP classification and the MELD scoring system, a poor prognosis was associated with higher preoperative cytokine concentrations, which suggests that both rating systems are useful for predicting the severity of the systemic inflammatory response in patients with end-stage liver disease. This result is consistent with those of Boin et al (2), Said et al (5), and Mishra et al (20), who suggested that both the CTP classification system and the MELD scores were equivalent for determining the outcome of patients suffering from chronic liver disease.…”
Section: Discussionsupporting
confidence: 92%
“…The MELD has been demonstrated to have a better ability in short‐term and intermediate‐term outcome prediction in comparison with the Child–Pugh score (14, 15). Nonetheless, the MELD still has potential limitations (16, 17). Hepatic encephalopathy, oesophageal varices bleeding and SBP are common complications associated with cirrhosis, which had been considered one of the allocation policies of liver providing.…”
Section: Discussionmentioning
confidence: 99%
“…MELD has been demonstrated to have a better ability in short-term or intermediate-term outcome prediction in comparison with the Child-Turcotte-Pugh (CTP) system [15][16][17] . Nonetheless, MELD still has potential limitations [18][19][20][21] . Hepatic encephalopathy, esophageal varices bleeding and spontaneous bacterial peritonitis are common complications with cirrhosis, which had been considered one of the allocation policies of liver providing.…”
Section: Discussionmentioning
confidence: 99%